2018
DOI: 10.1186/s12876-018-0821-z
|View full text |Cite
|
Sign up to set email alerts
|

Significantly different clinical features between hypertriglyceridemia and biliary acute pancreatitis: a retrospective study of 730 patients from a tertiary center

Abstract: BackgroundUnlike western world, gallstones and hypertriglyceridemia (HTG) are among the first two etiologies of acute pancreatitis (AP) in China. But yet, detailed differences in clinical features and outcomes between hypertriglyceridemia and biliary acute pancreatitis have not been well described.MethodsThis retrospective study enrolled 730 acute pancreatitis patients from July 1, 2013 to October 1, 2016 in Jinling Hospital. The causes of the study patients were defined according to specific diagnostic criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 26 publications
4
40
0
2
Order By: Relevance
“…Our study highlighted that there were more man(67.7% in MAP, 70.6% in MSAP and SAP) than woman(32.3% in MAP, 29.4% in MSAP and SAP) patients with young ages(39.8±11.0 in MAP, 39.7±11.0 in MSAP and SAP ) of HLAP, which was in line with the report of Li et al [10] . This phenomenon probably was responsible for strong work and life pressure, alcohol abuse, smoking, absent exercise, high-calorie food(such as high-fat diet, high-sugar diet), and irregular sleeping schedule in this group.…”
Section: Discussionsupporting
confidence: 92%
“…Our study highlighted that there were more man(67.7% in MAP, 70.6% in MSAP and SAP) than woman(32.3% in MAP, 29.4% in MSAP and SAP) patients with young ages(39.8±11.0 in MAP, 39.7±11.0 in MSAP and SAP ) of HLAP, which was in line with the report of Li et al [10] . This phenomenon probably was responsible for strong work and life pressure, alcohol abuse, smoking, absent exercise, high-calorie food(such as high-fat diet, high-sugar diet), and irregular sleeping schedule in this group.…”
Section: Discussionsupporting
confidence: 92%
“…Gallstones, alcohol abuse and massive hypertriglyceridemia (HTG) are generally thought to be three leading etiologies of AP worldwide [3]. However, unlike in Western countries, HTG, rather than alcohol abuse, is the second leading cause of AP in China [4]. Hypertriglyceridemiainduced acute pancreatitis (HTG-AP) is defined by serum triglyceride (TG) level exceeding 11.3 mmol/L (1000 mg/ dL) or between 5.6 to 11.3 mmol/L (500~1000 mg/dL) together with lipemic serum [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Still further, few studies highlighted that the outcome of HTG‐related AP has a more severe outcome. Li et al found higher rates of OF and complications in the HTG group compared to the biliary AP group, although no difference in the mortality was observed. While Zhu et al reported higher mortality in the HTG and alcohol groups compared to the biliary group, Zheng et al showed lower mortality rates in the HTG and biliary groups.…”
Section: Discussionmentioning
confidence: 96%